A monoclonal antibody raised against a thermo-stabilised β1-adrenoceptor interacts with extracellular loop 2 and acts as a negative allosteric modulator of a sub-set of 1- adrenoceptors expressed in stable cell lines - Soave, Mark; Cseke, Gabriella; Hutchings, Catherine J.; Brown, Alastair J.H.; Woolard, Jeanette; Hill, Stephen J. (Elsevier, 2018)
Recent interest has focused on antibodies that can discriminate between different receptor conformations. Here we have characterised the effect of a monoclonal antibody (mAb3), raised against a purified thermo-stabilised turkey β1-adrenoceptor (β1AR-m23 StaR), on β1-ARs expressed in CHO-K1 or HEK 293 cells. Immunohistochemical and radioligand-binding studies demonstrated that mAb3 was able to bind to ECL2 of the tβ1-AR, but not its human homologue. Specific binding of mAb3 to tβ1-AR was inhibited by a peptide based on the turkey, but not the human, ECL2 sequence. Studies with [3H]-CGP 12177 demonstrated that mAb3 prevented the binding of orthosteric ligands to a subset (circa 40%) of turkey 1-receptors expressed in both CHO K1 and HEK 293 cells. MAb3 significantly reduced the maximum specific binding capacity of [3H]-CGP-12177 without influencing its binding affinity. Substitution of ECL2 of tβ1-AR with its human equivalent, or mutation of residues D186S, P187D, Q188E prevented the inhibition of [3H]-CGP 12177 binding by mAb3. MAb3 also elicited a negative allosteric effect on agonist-stimulated cAMP responses. The identity of the subset of turkey β1-adrenoceptors influenced by mAb3 remains to be established but mAb3 should become an important tool to investigate the nature of β1-AR conformational states and oligomeric complexes.